Preliminary study on the role and mechanism of ISG15 in exosomes in platinum resistance in ovarian cancer - TIAN Yanan, ZHENG Hui, YAN Tianqing, ZHANG Heng, LU Renquan, GUO Lin (Zhongguo aizheng zazhi)
Background and purpose: Epithelial ovarian cancer (EOC) has a poor prognosis and is prone to developing resistance to platinum-based chemotherapy. Exosomes are currently believed to be involved in platinum resistance in ovarian cancer. This study explored the role and mechanism of exosomes on platinum resistance of ovarian cancer. Methods: Through ultracentrifugation, exosomes were isolated and analyzed using electron microscopy, particle size studies, and Western blot for detailed exosome analysis. We detected the expression levels of exosomal proteins and related signaling pathways. Exosomal protein expression profile was analyzed by proteomics. Key differential proteins were screened by intersecting with existing drug resistance datasets. Furthermore, patients diagnosed with EOC via pathological analysis at the Fudan University Shanghai Cancer Center from August 2023 to August 2024, who underwent surgery and fulfilled the eligibility requirements, were gathered to examine the link between the expression of interferon-stimulated gene 15 (ISG15) in serum exosomes and resistance to platinum medication. The expression levels of related proteins in serum exosomes were quantitatively detected by enzyme-linked immunosorbent assay (ELISA). Receiver operating characteristic (ROC) curve was plotted to explore the predictive value of serum exosomal protein in ovarian cancer resistance. Results: Exosomes derived from platinum-sensitive and drug-resistant ovarian cancer cells were extracted and proteomic analysis was further performed. We identified 9 differential proteins associated with platinum-resistance and found the key molecule interferon-stimulated gene 15 (ISG15). Compared with sensitive cells, the expression of ISG15 in exosomes of drug-resistant ovarian cancer cells was significantly upregulated. Exosome tracer tests showed that exosomes were successfully taken up by ovarian cancer receptor cells. After coculture with drug-resistant exosomes, the expression level of ISG15 in ovarian cancer receptor cells was increased. Knockdown ISG15 in EOC cells decreased the expression of ISG15 in exosomes, and incubation of ISG15-knockdown exosomes decreased the cell viability on the condition of platinum drugs, indicating that ISG15 in exosomes regulated platinum resistance of ovarian cancer cells. Moreover, ISG15 could regulate the expression of multidrug resistance protein 1 (MDR1) through phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/nuclear factor-kappa-light-chain-enchancer of activated B cells (NF-κB) signaling pathway. This study included a total of 87 patients. Clinical serum samples also showed that the expression of ISG15 in exosomes was higher in platinum-resistant ovarian cancer patients than in sensitive ovarian cancer patients. Using serum exosomal ISG15 as an indicator to distinguish between sensitivity and resistance, the area under ROC curve was 0.779 (P<0.05), cutoff value was 27.35ng/mL, sensitivity was 70.2%, and specificity was 76.4%. Conclusion: ISG15 in exosomes can regulate the expression of MDR1 in ovarian cancer cells through PI3K/AKT/NF-κB signaling pathway, and promote platinum resistance in ovarian cancer cells.